Developments in the amended Sharia procedures law for the year 2016 regarding notification - Alsahouri, Reem Amin (Journal of Economic, Administrative and Legal Sciences, 2022)
This research aimed at shedding light on the most prominent amendments that were made to the Code of Shari’a Procedures No. (31) of 1959 and its amendments until 2016. This research also aims to highlight the role of these amendments in addressing deficiencies in the field of notification, and to indicate its strengths and weaknesses. And the effectiveness of these amendments in filling the gaps. In his research, the researcher relied on the inductive method, by following the legal articles on which the amendment was made, and also relied on the analytical method by analyzing those amendments and showing their impact and the changes they made to the reporting process. The researcher concluded that the most important amendments to the notification were: the adoption of electronic methods in correspondence between the courts and notification exchanges. The law also permitted the notification of litigants by one or more companies approved by the judge of the judges, in addition to special measures for the record to ensure that notification is carried out in accordance with the rules, as stipulated The law states that it is permissible to take a chosen domicile for the purposes of notification for those who reside outside the Kingdom, and grants the legitimate Public Prosecution the power to summon and fetch those whom it deems useful or necessary in summoning them.